Pengaturan Motor Induksi Meggunakan Chopper Pada Rotor Berbasis Komputer - Abdul Haris (Electrician : Jurnal Rekayasa dan Teknologi Elektro, 2009)
Usually the speed control used the electronic instruments, for example it is based on a microcontroler. For easy controlling, microcontroller is connected to computer as a bridge between user and the motor that is to be controlled. The speed of induction motor for wound rotor type is adjustable by using the chopper that is connectedto its rotor circuit. With the use of the power transistor as a chopper, so switching can be manipulated and easy to control. The control instrument is made by using microcontroller that based on computer. The speed control used a chopper circuit results in the wider speed control depending on the duty cycle of the chopper. While by using the conventional external resistor just results in the speed control area that its condition depends on the variable resistors used.